1996
DOI: 10.1111/j.1365-2052.1996.tb00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interbreed genetic variations of mitochondrial DNA major non‐coding regions in Japanese native dog breeds [Canis familiaris)

Abstract: Mitochondria1 DNA (mtDNA) major non-coding regions were amplified from 73 dogs of eight Japanese native dog breeds and from 2 1 dogs of 16 non-Japanese dog breeds by the polymerase chain reaction and their DNA sequences were determined. A total of 51 nucleotide positions within the non-coding region (969-972 base pairs) showed nucleotide variations of which 48 were caused by transition. These nucleotide substitutions were abundant in the region proximate to tRNAPr0. In addition to the nucleotide substitutions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 29 publications
4
51
1
4
Order By: Relevance
“…The ternary site 15639 brought mutations in a total of 28 hgs (87.5%), where a transversion to A was observed in 20 hgs (62.5%) and a transversion to G in 8 hgs (25%). The positions located in HVS-I were also found to be highly polymorphic in previous studies [12,14,[22][23][24], partly using other nomenclatures for base designation (Table S3). In Angleby and Savolainen [14], position 15627 showed a mutation in 49 hgs (39.5%), position 15639 in 109 hgs (88%; 73 hgs [59%] harboured the variant A, 36 hgs [29%] showed a G) and position 15955 displayed a mutation in 48 hgs (39%); in Savolainen et al [24], position 15627 showed a G in 75 hgs (48%) and even one transversion (A-T, W11), position 15639 displayed a mutation in 139 hgs (90%), where 106 hgs (68%) showed an A and 33 hgs showed a G (21%), of which two had a deletion at this position, and position 15955 showed a mutation in 51 hgs (33%).…”
Section: Hot Spotsmentioning
confidence: 68%
See 4 more Smart Citations
“…The ternary site 15639 brought mutations in a total of 28 hgs (87.5%), where a transversion to A was observed in 20 hgs (62.5%) and a transversion to G in 8 hgs (25%). The positions located in HVS-I were also found to be highly polymorphic in previous studies [12,14,[22][23][24], partly using other nomenclatures for base designation (Table S3). In Angleby and Savolainen [14], position 15627 showed a mutation in 49 hgs (39.5%), position 15639 in 109 hgs (88%; 73 hgs [59%] harboured the variant A, 36 hgs [29%] showed a G) and position 15955 displayed a mutation in 48 hgs (39%); in Savolainen et al [24], position 15627 showed a G in 75 hgs (48%) and even one transversion (A-T, W11), position 15639 displayed a mutation in 139 hgs (90%), where 106 hgs (68%) showed an A and 33 hgs showed a G (21%), of which two had a deletion at this position, and position 15955 showed a mutation in 51 hgs (33%).…”
Section: Hot Spotsmentioning
confidence: 68%
“…In agreement with [21], the importance of a unique standardized reference sequence is also emphasized here, as the application of different reference sequences confuses the reporting of mtDNA haplotypes [12,15,20,[22][23][24]28]. Table S3 presents some different notations of already established data in a comparative way [12,20,22,23] to help harmonization of results.…”
Section: Notation Of the Canine Crmentioning
confidence: 93%
See 3 more Smart Citations